(untitled) (Modern education and development, 2025)
This article analyzes in detail the kinematics of fluid motion inside the impeller of centrifugal pumps. The absolute, relative and peripheral velocity components of the flow, velocity triangles, flow angles and their effect on efficiency are considered. Flow disturbances, separation zones, twisting motions (vortices) and methods for eliminating them are also covered. Based on kinematic analysis, the possibilities of determining theoretical pressure using the Euler equation and other hydraulic formulas, and evaluating flows using computer modeling (CFD) are also considered. The article is intended for engineers and technical specialists involved in pump design, hydraulics and energy efficiency.